Membandingkan Metode Simple Addictive Weighting (SAW) dan Multifactor Evaluation Process (MFEP) Dalam Penentuan Jurusan Sma Negeri 10 Padang - Deny Suyandi; Rini Sovia; Aulia Fitrul Hadi (Majalah Ilmiah UPI YPTK, 2019)
Decision support system is a combination of individual intelligence sources with the ability of components to improve the quality of decisions. Decision support systems are also computer-based information systems for management decision-making that deal with semi-structured problems. With a decision support system makes it easier for us to determine the decisions for majors of high school students. Because the determination of this department is very influential with the future of students. So from that the author conducted this study to facilitate students in determining majors. So that these two methods can be compared and find the best results in making decisions about the majors of high school students.